Between Communist Doctrines and Nationalist Agendas: Writing Reforms in Inner Mongolia, 1954–1980. (November 2021) - Wang, Anran
The writing reforms of the Mongolian language in Inner Mongolia from 1954 to 1980 are a notable case of Maoist China's language planning projects. In those years, the Chinese government attempted to implement two consecutive reforms featuring Cyrillization and Latinization of the Mongolian writing system, but neither reform yielded any substantial result and the traditional Mongolian script remains in use today. This article explores the domestic and international dynamics behind these two closely related reform attempts and examines their origins, rationales, processes of implementation, and reasons for failure. Although the rationales of both reforms lay in the communist doctrine favoring easier, more regular, and more universal writing systems that could improve literacy and facilitate communication, hidden behind both reforms were nationalist agendas. The Cyrillization reform sought linguistic unity with the Mongolian People's Republic, while the Latinization reform sought unity of writing systems among languages in China. In both cases, the hidden nationalist agendas undermined the original goals of the reforms, and the reforms lost momentum once contending agendas prevailed.